A Study of Women Empowerment: Decision Making and Participation in Farm & Household Economic Activities - Roy , M.L.; Kadian, K.S. (Indian Journal of Extension Education, 2016)
Women empowerment especially economic empowerment is very important as it gives security to a woman. It is very  crucial for progress of the society. Women plays a pivotal and potentially benefiting role in all-round growth of resource poor farm families. But often they are neglected in decision making on farm and household matters which are mostly  managed by them. Participation in decision making process especially in economic activities is an indication of  empowerment. The present study attempts to investigate the level of women economic empowerment in resource-poor  farm families by analyzing their extent of participation in decision making on farm and household related economic  activities. The study was conducted in six agro-climatic zones of West Bengal taking a random sample of 120 resource poor farm families. Both husband and wife of the families were personally interviewed by pretested structured interview  schedule. Spearman's rank-difference correlation was used to measure the extent of agreement between husband's and  wife's responses. The study revealed that wives played a major role to jointly decide purchasing or hiring of land (43.33- 47.50 %), selling of produce (35.00-35.83 %) and borrowing for agriculture (26.67-30.00 %). Decisions for milking and  processing of milk, utilization of dung and sale of milk and milk products were dominantly taken by wives (72.50 per cent,  54.67 per cent and 40.83 per cent, respectively), where purchase and sale of animals, type and number of animals to be  kept and adoption of new animal husbandry practices were mainly decided jointly (32.50-37.50 per cent, 31.67-36.67 per  cent and 24.17-27.50 per cent, respectively). Household economic decisions on building new house, household  purchasing, education of children, selection of occupation for children and financial activities were mainly taken jointly  (38.33-41.67 per cent, 32.50-35.83 per cent, 25.00-27.50 per cent, 25.83-30.00 per cent and 24.17-27.50 per cent,  respectively). The findings of the study indicated higher level of women economic empowerment in animal husbandry  and household sectors.
Keywords: Women economic empowerment; decision making; resource-poor farm family; spearman's rank-difference correlation